Preparing Vocational High School Students for the Industrial Revolution 5.0 with Reading and Writing Literacy Using ChatGPT - Samroh (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
The industrial revolution transformed manufacturing by shifting from traditional hand-based methods to machine use. Currently in the era of Industrial Revolution 4.0, characterized by advancements in IT, automation, big data, robotics, AI, and IoT, we are moving towards Industrial Revolution 5.0, which integrates advanced technology with human skills for more efficient, flexible, and sustainable production. This technological development impacts future labor market demands, necessitating educational adaptation to develop digital era skills. Vocational education and training are crucial for preparing individuals for automated and connected jobs. Vocational High Schools (SMKs) must equip students to meet the workforce trends of the Industrial Revolution 5.0